Countering International Extremism - M. S. Karimova (Евразийская интеграция: экономика, право, политика, 2021)
The article is devoted to the study of countering international extremist activity features, including the intensifying corresponding Internet threats. The author notes that in modern conditions, threats of extremism require an integrated approach at the national and international levels, more effective mobilization of state and interstate forces and resources (financial, information, etc.), including acts of blocking relevant contacts and illegal virtual resources. The article contains statistical data showing an increase in extremist threats, including the youth environment, and, accordingly, the need to intensify and expand measures to counter such negative phenomena.